Biologically Active α-Amino Amide Analogs and γδ T Cells—A Unique Anticancer Approach for Leukemia - Otaibi, Ahmed Al; Sherwani, Subuhi; Al-Zahrani, Salma Ahmed; Alshammari, Eida Mohammed; Khan, Wahid Ali; Alsukaibi, Abdulmohsen Khalaf D.; Khan, Shahper Nazeer; Khan, Mohd Wajid Ali (Frontiers in Oncology, 2021)
Advanced stage cancers are aggressive and difficult to treat with mono-therapeutics, substantially decreasing patient survival rate. Hence, there is an urgent need to develop unique therapeutic approaches to treat cancer with superior potency and efficacy. This study investigated a new approach to develop a potent combinational therapy to treat advanced stage leukemia. Biologically active α-amino amide analogues (RS)-N-(2-(Cyclohexylamino)-2-oxo-1-phenylethyl)-N-phenylpropiolamide (α-AAA-A) and (RS)-N-(2-(Cyclohexylamino)-2-oxo-1-phenylethyl)-N-phenylbut2-enamide (α-AAA-B) were synthesized using linear Ugi multicomponent reaction. Cytotoxicities and IC50 values of leukemia cancer cell lines (HL-60 and K562), were analyzed though MTT assay. Cytotoxic assay analyzed percent killing of leukemia cell lines due to effect of γδ T cells alone or in combination with α-AAA-A or α-AAA-B. Synthesized biologically active molecule α-AAA-A exhibited increased inhibitions of HL-60 (54%) and K562 (44%) proliferation compared to α-AAA-B (44% and 36% respectively). Similarly, α-AAA-A showed low IC50 values for HL-60 (1.61 ± 0.11 μM) and K562 (3.01 ± 0.14 μM) compared to α-AAA-B (3.12 ± 0.15 μM and 6.21 ± 0.17 μM respectively). Additive effect of biologically active molecule and γδ T cells showed significantly high leukemia cancer cells killing as compared to γδ T cells alone. A unique combinational therapy with γδ T cells and biologically active anti-cancer molecules (α-AAA-A/B), concomitantly may produce promising cancer therapy.